2022
DOI: 10.1186/s12916-022-02678-6
|View full text |Cite|
|
Sign up to set email alerts
|

Links between electroconvulsive therapy responsive and cognitive impairment multimodal brain networks in late-life major depressive disorder

Abstract: Background Although electroconvulsive therapy (ECT) is an effective treatment for depression, ECT cognitive impairment remains a major concern. The neurobiological underpinnings and mechanisms underlying ECT antidepressant and cognitive impairment effects remain unknown. This investigation aims to identify ECT antidepressant-response and cognitive-impairment multimodal brain networks and assesses whether they are associated with the ECT-induced electric field (E-field) with an optimal pulse amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 59 publications
(64 reference statements)
1
2
0
Order By: Relevance
“…In contrast, ST a was unrelated with cognitive outcomes. The strong association between E brain /I and cognitive outcomes replicates our previous work and adds support for the role of E brain /I in ECT dosing [14,54]. In this sample, an E brain /I of 0.15 V/m/mA was the maximal associated with stable cognitive performance with traditional fixed amplitude 800 mA dosing.…”
Section: Cognitive Outcomessupporting
confidence: 86%
“…In contrast, ST a was unrelated with cognitive outcomes. The strong association between E brain /I and cognitive outcomes replicates our previous work and adds support for the role of E brain /I in ECT dosing [14,54]. In this sample, an E brain /I of 0.15 V/m/mA was the maximal associated with stable cognitive performance with traditional fixed amplitude 800 mA dosing.…”
Section: Cognitive Outcomessupporting
confidence: 86%
“…Recent studies demonstrated links between ECT therapy response and multimodal brain networks in LLD. Volume increases in the hippocampal complex and thalamus were antidepressant response-specific, while functional decreases in amygdala and hippocampus complex were CI-specific, the overlap between antidepressant-response and CI networks challenges parameters of ECT implicating individualized treatment modules (Qi et al 2022 ).…”
Section: Brain Changes Following Lld Treatmentmentioning
confidence: 99%
“…The original article [ 1 ] mistakenly omitted panel (g) from Figure 1; the panel has since been re-inserted.…”
mentioning
confidence: 99%